Clinical management of behavioral characteristics of Prader–Willi syndrome - Alan Y Ho (Dove Medical Press, 2010)
Alan Y Ho, Anastasia DimitropoulosDepartment of Psychology, Case Western Reserve University, Cleveland, OH, USAAbstract: Prader–Willi syndrome (PWS) is a complex neurodevelopmental disorder caused by an abnormality on the long arm of chromosome 15 (q11–q13) that results in a host of phenotypic characteristics, dominated primarily by hyperphagia and insatiable appetite. Characteristic behavioral disturbances in PWS include excessive interest in food, skin picking, difficulty with a change in routine, temper tantrums, obsessive and compulsive behaviors, and mood fluctuations. Individuals with PWS typically have intellectual disabilities (borderline to mild/moderate mental retardation) and exhibit a higher overall behavior disturbance compared to individuals with similar intellectual disability. Due to its multisystem disorder, family members, caregivers, physicians, dieticians, and speech-language pathologists all play an important role in the management and treatment of symptoms in an individual with PWS. This article reviews current research on behavior and cognition in PWS and discusses management guidelines for this disorder.Keywords: Prader–Willi syndrome; neurodevelopment, hyperphagia, disability